Women Farmers’ Perceived Impact and Acceptability of the Ongoing Agrcultural Development Programmes in Enugu State - M U Dimelu; E M Igbokwe; A O Obieri (Journal of Agricultural Extension, 2009)
The study appraised the National Special Programme for Food Security (NSPFS), Root and Tuber Expansion Programme (RTEP) and Presidential Initiative on Increased Cassava Production, Processing and Export (PICPPE) in Enugu State using women beneficiaries. Data were collected from 270 randomly selected women by use of interview schedule. Simple descriptive statistics and analysis of variance (ANOVA) were used for data analysis. The programmes had similar and complementary baseline conditions. The women expressed acceptance of the baseline condition, but NSPFS baseline condition was more acceptable than that of RTEP and PICPPE with total mean scores of 4.4, 4.1 and 2.7, respectively. There was no significant difference in the impact of the programmes across the zones. Generally, the programmes were gender sensitive, but the popular poor access of women to production resources calls for greater investment on capacity building and sustained institutional support. Also given the market driven agricultural development trends across the globe, development intervention should essentially incorporate appropriate policy, legislative, and information system for sustainability and optimum impact.